Comparative efficacy and tolerability of ferric pyrophosphate vs ferrous sulfate in pediatric iron deficiency anemia: a 6-month randomized controlled trial - Inderdeep Singh Kochar; Dilpreet Kaur; Money Sachdeva (Egyptian Pediatric Association Gazette)
Abstract Background Iron deficiency anemia (IDA) remains one of the leading causes of childhood morbidity worldwide. Conventional therapy with ferrous sulfate is often limited by gastrointestinal (GI) side effects and poor adherence. Ferric pyrophosphate (FPP), a newer iron formulation, promises improved tolerance and equivalent efficacy. This study aimed to compare the efficacy and safety profile of FPP versus ferrous sulfate in the management of pediatric IDA. Methods A randomized controlled trial was conducted at a tertiary care center, enrolling 120 children aged 6 months to 12 years with IDA. Participants were randomly assigned to receive either FPP (1 mg/kg/day) or ferrous sulfate (3 mg/kg/day) for 6 months. Hemoglobin (Hb), serum ferritin, GI side effects, and compliance were assessed at baseline, 3 months, and 6 months. Results Both groups demonstrated a significant improvement in Hb levels, with the mean Hb rise being 3.1 g/dL in the FPP group and 3.3 g/dL in the FS group (p = 0.34). GI side effects were significantly lower in the FPP group (12%) compared to the FS group (41%) (p < 0.01). Compliance was also better in the FPP group (p < 0.001). Conclusion Ferric pyrophosphate is as effective as ferrous sulfate in correcting anemia and improving iron stores in children, with a significantly better tolerability profile. It presents a promising alternative to conventional iron therapy in pediatric IDA.